Elevated Concentration of Defensins in Hepatitis C Virus-Infected Patients - Ehab H. Mattar; Hussein A. Almehdar; Abdullah A. AlJaddawi; Isam ElDin M. Abu Zeid; Elrashdy M. Redwan (Journal of Immunology Research)
Hepatitis C virus (HCV) is the major etiological agent of human non-A and non-B hepatitis, affecting around 180 million people worldwide. Defensins, small cysteine-rich cationic peptides, are shown to have potent antibacterial, antiviral, and antifungal properties. Defensins can be found in both normal and microbial infected patients, at variable concentrations. Notably, viral infections are often associated with elevated concentrations of defensins. The current study aimed to estimate the concentrations of total, α-, and β-defensins in serum taken from normal and HCV-infected patients. 12 healthy (noninfected) and 34 HCV-infected patients were enrolled. Standardized immunoassay kits were used to obtain serum concentrations of defensins. The obtained results were calibrated against kit standard reagents. Total defensin concentrations in HCV-infected patients were significantly higher (2- to 105-fold) compared to healthy individuals. The concentrations of α-defensins were also significantly elevated in the HCV-infected patients (31–1398 ng/50 μL). However, concentrations of β-defensins ranged from 44.5 ng/50 μL to 1056 ng/50 μL. The results did not reveal differences in serum defensin concentration between male and female HCV-infected patients. A-defensin concentration of ≥250 ng/50 μL was found to contain more β-defensins than total defensins and α-defensins. This study concludes, for the first time, that serum defensin levels are elevated in HCV-infected patients.